PENDAMPINGAN DESAIN PERENCANAAN KANTOR BALAI DESA GALEH KECAMATAN TANGEN KABUPATEN SRAGEN - susanti, riza (Jurnal Pengabdian Vokasi, 2023)
Galeh Village in Tangen District, Sragen Regency has a village head's office or what is usually referred to as a village hall as the center of government and administration at the village level. The village hall is a village-owned building where village residents gather when holding meetings, conferences or deliberations. Apart from holding important meetings to discuss matters related to the village, the village hall also often functions as a place for social activities to take place. Conditions in the field, the village hall office is experiencing problems such as many rooms that are not being used, are outdated, and circulation that is not up to standard. Applying the Neo Vernacular Architectural Concept to the Galeh Village Hall is a solution to the redesign of the hall. The combination of traditional and modern architecture is a characteristic of this architectural concept which can be seen from maintaining the joglo roof, adding batik ornaments and elephant tusk monuments to the building which are characteristic of the Javanese culture of the local community. then combined with the use of modern materials such as brick walls, roster windows, GRC list plans and others.